Healthy but risky: A descriptive study on cyclists' encouraging and discouraging factors for using bicycles, habits and safety outcomes. (April 2019) - Useche, Sergio A.; Montoro, Luis; Sanmartin, Jaime; Alonso, Francisco
Highlights: This study addressed encouraging and discouraging factors influencing cyclists' decision to use the bike. The data was collected from 1064 cyclists from 20 different countries. Physical health, environmental sustainability and economy were the main factors encouraging cycling. Perceived crash risk, adverse weather conditions and lack of safety were found to be the most relevant discouraging factors. Individuals cycling with more regularity were found to be less prone to suffer cycling crashes. Abstract: Transportation is a necessary process that requires not only adequate means, but also individual choices. And apparently, the recent boom of alternative modes of transportation has substantially changed people's perceptions of cycling, as well as the reasons why they decide to use a bike. Nevertheless, people identify some motives that encourage this use together with the perceived risks and the discouraging factors which affect the choice of using a bike, thus making it important to explore all these elements in the light of the empirical evidence. The objective of this study was to explore and describe the encouraging and discouraging reasons behind the use of bikes among cyclists, together with the reasons behind their journeys and the relationship of these elements with their crash history. For this study, 1064 cyclists were asked to complete an electronic survey which gathered information on their cycling-related habits, perceptions and motives. The results show that physical health and fitness (38%), contribution to environmental sustainability (14%), economy (13%) and time saving (10%) were the most frequent factors which encouraged cycling. On the other hand, perceived crash risk (17%), adverse weather conditions (17%) and lack of safety (16%) were found to be the most relevant discouraging factors. Finally, participants who cycled with more regularity were found to be less prone to suffer cycling crashes. The findings of this study support that cycling is a choice based on both benefits and risks, and its perceived connection to health is highly prevalent among active cyclists. Furthermore, perceived risks which may discourage cycling are an issue that needs to be addressed by transport policies, in order to enhance the engagement of the population in this mode of transportation. Also, this study highlights the need to strengthen utility cycling (cycling for transport to and from places) as a way to integrate transportation within healthier practices and habits.